2019
DOI: 10.1002/tesj.494
|View full text |Cite
|
Sign up to set email alerts
|

Nonnative‐English‐speaking teacher candidates’ language teacher identity development in graduate TESOL preparation programs: A review of the literature

Abstract: This systematic review synthesizes 17 studies exploring nonnative-English-speaking teacher candidates' (NNES-TC) language teacher identity (LTI) development. The purpose was to examine NNES-TCs' LTI development during graduate-level TESOL programs in the United States, Canada, and Australia. The review addressed the questions, What influences NNES teacher candidates' LTI development, and in what ways do teacher preparation programs promote positive LTI development? Findings revealed four categories: (1) (non)n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
0
8
0
2
Order By: Relevance
“…In the literature, there are studies examining the oral expression levels and speaking skills of preservice teachers (Yelok & Sallabas, 2009). In addition, it is seen that studies emphasise the necessity of improving the speaking skills of teachers and teacher candidates (Swearingen, 2019;Vostal, Mrachko, Vostal, & McCoy, 2021). Akkaya (2012) examined the speech problems experienced by pre-service teachers and stated that among these problems, under the title of psychological problems, students have speaking problems in public.…”
Section: Related Researchmentioning
confidence: 99%
“…In the literature, there are studies examining the oral expression levels and speaking skills of preservice teachers (Yelok & Sallabas, 2009). In addition, it is seen that studies emphasise the necessity of improving the speaking skills of teachers and teacher candidates (Swearingen, 2019;Vostal, Mrachko, Vostal, & McCoy, 2021). Akkaya (2012) examined the speech problems experienced by pre-service teachers and stated that among these problems, under the title of psychological problems, students have speaking problems in public.…”
Section: Related Researchmentioning
confidence: 99%
“…The emergence and establishment of the Global Englishes paradigm correlated with a substantial body of research, teaching, and advocacy efforts that challenge, redefine and recontextualize the characteristics of a native speakerist worldview evident in ELT, as a profession, activity, and area of scholarly inquiry. Therefore, we have been witnessing tremendous interest and scholarly productivity in "NEST/NNEST studies" (see Figure 1 Moussu & Llurda (2008); Kamhi-Stein (2014); Llurda (2016); Swearingen (2019); Selvi (2014Selvi ( , 2019; Yuan (2019) Conceptual articles Maum (2002); Rudolph et al (2015); Kamhi-Stein (2016) Theses/dissertations Llurda (2003); Mahboob (2003); Moussu (2006); Faez (2007); Reis (2010); Aneja (2016); Karas (2019) Newsletter TESOL International Association's "Nonnative" English Speakers in TESOL (NNEST) Interest Section Newsletter Other Institutionalized responses against discrimination in ELT (press release, white papers, position statements), blogs, online advocacy groups, groups in social networking sites…”
Section: The Scope Of the "Nest/nnest Studies 3 "mentioning
confidence: 99%
“…Barkhuizen, 2016;Kanno & Stuart, 2011;Varghese vd., 2016;Yazan, 2018) neticesinde bazı bilim adamlarının "anadili İngilizce olan/olmayan öğretmen çalışmaları" (NEST/NNEST studies) (Kirkpatrick, 2010;Llurda, 2018) olarak adlandırdığı bir araştırma alanının ortaya çıktığı söylenebilir. Yıllar boyunca, pek çok araştırmacı bu alanda ortaya çıkan gelişmeleri kapsamlı olarak değerlendiren ve eleştiren yazılar ortaya koysa da (Kamhi-Stein, 2016;Llurda, 2016;Medgyes, 1992;Moussu & Llurda, 2008;Rudolph vd., 2015;Selvi, 2019a;Swearingen, 2019;Yuan, 2019), alan yazında ülke bazında yapılan sistematik değerlendirmelerin eksikliği aşikardır. Bu gereksinimden hareketle, bu çalışma Türkiye bağlamında "anadili İngilizce olan/olmayan öğretmen çalışmaları" alanında son yirmi yılda yapılan (43'ü hakemli dergi makalesi, 7'si kitap bölümü, 26'sı yüksek lisans tezi ve 9'u doktora tezi olmak üzere) toplam 85 çalışmanın bir kapsam incelemesini sunmaktadır.…”
Section: Geni̇ş öZetunclassified
See 1 more Smart Citation
“…As there is a pressing need to understand student‐teachers’ background in order to calibrate programs’ aims with student‐teachers’ prior knowledge and experiences (Charteris, Thomas, & Masters, 2018), scholars have examined identity processes and transitions of student‐teachers (Henry, 2016; Nguyen & Dao, 2019; Swearingen, 2019; Timŏstšuk & Ugaste, 2010; Trent, 2013; Villacañas de Castro, 2020; Wolff & De Costa, 2017). These studies have revealed the complexity of teacher identity construction and how it is affected by prior experiences, imagined selves, and emotions (Song, 2016; Wolff & De Costa, 2017).…”
Section: Introductionmentioning
confidence: 99%